Pengaruh Kepemimpinan, Kompensasi dan Motivasi Kerja terhadap Kinerja Pegawai Pada Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat - Rahmad, Rahmad (Jurusan PIPS FKIP UMMY Solok, 2019)
This study aims to reveal: 1. The influence of leadership on employee performance. 2) Effect of Compensation on employee performance. 3) The Effect of Work Motivation on the performance of employees. 4) The effect of leadership on Work Motivation. 5) Effect of Compensation on Work Motivation at the Institute of Domestic Administration of the West Sumatera Campus. The population in this study were non-PNS employees of the Institute of Internal Affairs of the West Sumatera Campus, amounting to 89 people consisting of 1) Administration Section, 2) Academic and Collaborative Section, 3) Research Section, 4) Cultivation Unit, 5) Computer Unit and Language, 5) Government Laboratory Unit. The sample collection in this study used the census method, which is 89 employees of the Non PNS Institute of Domestic Administration, West Sumatera Campus. The analytical tool used is Path Analysis using the SPSS program (Statistical Package For Social Science). The findings of this study are: 1) Leadership has a significant and positive effect on the Work Motivation. 2) Compensation has a significant and positive effect on the Work Motivation. 3) Leadership has a significant and positive effect on Employee Performance with Work Motivation as a mediator between leadership and Employee Performance 4) Compensation has a significant and positive effect on Employee Performance with Work Motivation acts as a mediator between compensation and Employee Performance 5) Work motivation has a significant and positive effect on Employee Performance at the Sumatera Campus Institute of Domestic Administration.